PROBLEMS OF PREVENTING CRIMES COMMITTED USING THE INTERNET - Allanova Azizakhon Avazxonovna (International Journal of Business, Law and Political Science, 2024)
This scientific article describes the problems of preventing crimes committed using the Internet, crime prevention, the specific characteristics of crimes committed in cyber space, the analysis of crimes committed using the Internet in the criminal laws of some foreign countries.